Walking with giants : the extraordinary life of an ordinary man : a memoir - Towns, Elmer L. (Ventura, Calif. : Regal, 2012)
"Walking with Giants is Elmer Town's story, in his own words, from his struggles as an adolescent to accepting salvation to pastoring his first congregation at the age of 19. You will read about the doors God opened for Elmer and his friend Jerry Falwell to found Liberty University and about the school's incredible growth over the past 40 years. Above all, you will see the faithful hand of God at work for His glory in the life of an ordinary man - and know without a doubt that He can work in you, too." - Back cover.
The early years: birth through elementary school (1932-1943) -- The high school years (1945-1950) -- The Columbia Bible College years (1950-1953) -- The Northwestern years: the long, cold, dark winter's night (1953-1954) -- The Dallas Theological Seminary years (1954-1958) -- The Midwest Bible College years (1958-1961) -- The Canadian years (1961-1965) -- The Trinity Evangelical Divinity School years (1965-1971) -- The early Liberty University years (1971-1973) -- A desert experience in the interim years (1973-1977) -- Great ministry at Liberty (1977-1952) -- A new century (2000-2011).
Includes bibliographical references (p. [253]-256) and index.
Keywords: Towns, Elmer L; Baptists -- United States -- Clergy -- Biography